The prince of Venice Beach - Nelson, Blake, 1965- (Little, Brown and Company, 2014)
Robert "Cali" Callahan, seventeen, gets swept up into the private-investigator business and must deal with the ramifications of looking for fellow runaways who may not want to be found--and with falling in love with one of them.